Targeted investments in elite sport funding: wiser, more innovative and strategic? - Sam, M. (Managing Sport and Leisure, 2012)
Targeting funds to a select `few` organisations is an increasingly recognised principle of government funding distributions for elite sport. This paper explores the principles of performance-based targeting in sport and traces its historical development alongside New Public Management reforms. Drawing from data in New Zealand, it is suggested that targeting schemes generate unintended consequences including: (a) the paradoxical tendency for the central agency to be blamed for having too much control over sport and for not being sufficiently accountable for results and (b) the propensity for National Sport Organisations (NSOs) to become less innovative over time due to increased accountability requirements and tighter monitoring. Each carries implications. The former reminds us that broader political risks cannot be ruled out, and may effectively negate targeting's promise of allocative efficiency and responsiveness. The latter warns that such regimes may hinder organisational learning and induce NSOs to follow `best practice` at the expense of developing new best practice.